Preconditions of an Intercultural Communication - Hrubec, Marek (Communication Today, 2025)
The article deals with the issue of intercultural communication, especially concerning a potential for consensus among cultures by means of an intercultural dialogue on human rights. It is a contribution towards overcoming the confrontations among civilizations and to the eradication of the coercive imposing of human rights onto other cultures. The paper demonstrates that the intercultural promotion of human rights across individual cultures that recognize each other is one of the effective forms of resistance against people being misrecognized. However, this requires a formulation of human rights based on the values of individual cultures and the dialogue among them. The interpretation of the paper is a contribution to creating ‘unity in plurality’, i.e. a universality of human rights within the plurality of cultures.